Some Insect Pests (Arthropoda: Insecta) of Summer Vegetables, Their Identification, Occurrence, Damage and Adoption of Management Practices - Sarwar, Muhammad (International Journal of Sustainable Agricultural Research, 2014)
Vegetable is an edible plant or its part, intended for cooking or eating raw, whose fruits, seeds, roots, tubers, bulbs, stems, leaves, or flower parts are used as food. Vegetables are relatively cheaper and rich source of vitamins, carbohydrates, proteins and minerals. Their consumption gives taste, palatability, fiber for digestion, increases appetite and checks constipation. The objective of this article is to assess the some insect pests of summer vegetables, their identification, occurrence, damage and adoption of management practices. Various insects and mites cause damage to vegetable plants at all stages of growth including aphid, thrip, whitefly, leafhopper, two spotted spider mite, squash bug, pumpkin beetles, flea beetles, hadda or epilachna beetles, eggplant shoot and fruit borer, cutworms, hornworms, tomato fruit borer, tobacco caterpillar and melon fruit fly. Most of the vegetables are susceptible to pest damage, and their seeds, roots, stems, leaves as well as fruits are all subjected to injury. Vegetables damage ranges from reduced plant vigor to plant death and ultimately heavy crop losses occur. A combination of pest control strategies is of paramount importance and usually works well to reduce damage and keep the insect population below economic injury level for minimizing the yield loss. Pest identification of the vegetables is the most important step and the correct identification of pest troubles is the beginning of a successful integrated pest management program. The integrated pest management (IPM) include use of mechanical and cultural strategies, use of tolerant plant varieties, growing healthy seedlings, practicing adequate field sanitary measures particularly removing the fallen leaves, buds or debris, undertaking weekly field checking to spot out the presence of the insects, conservation of natural control agents, application of need based insecticides and ensuring of community approach for all the suggested tactics to maximize benefits.